Community-led water services for multiple uses: Pathways from water to nutrition in research and action - van Koppen, Barbara (2020)
In this presentation I will focus on impact pathways from water management to improved nutrition, in particular for the majority of malnourished infants, children and adults, so in low-income rural areas. I will try to compare impact pathways in current research with pathways that these rural communities perceive, according to studied practices. I will argue that communities’ perspectives fill a gap in current research. Filling that gap helps move to action. I will conclude with two recent examples of such action: supported self supply and community-driven water services for multiple uses.